Experimental Simulation and Characterization of Radiation Damage in Materials - Krsjak, Vladimir (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to advance the current knowledge in ion irradiation studies and accelerated ageing of materials. The collected papers address various areas in the field, from the fundamentals of ion beam irradiation to innovative experimental characterization of the materials and related theoretical modelling. The present research contributes primarily to the understanding of the applied aspects of ion bombardment as a surrogate for neutron irradiation and a tool for experimental simulation of harsh radiation environments. At the same time, this Special Issue features several exciting studies on the microstructural characterization of the radiation tolerance of materials across a broad spectrum of scientific and industrial areas.